2021
DOI: 10.1007/s13280-020-01482-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of human pressures on Europe’s marine ecosystems

Abstract: Marine ecosystems are under high demand for human use, giving concerns about how pressures from human activities may affect their structure, function, and status. In Europe, recent developments in mapping of marine habitats and human activities now enable a coherent spatial evaluation of potential combined effects of human activities. Results indicate that combined effects from multiple human pressures are spread to 96% of the European marine area, and more specifically that combined effects from physical dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 40 publications
4
39
0
Order By: Relevance
“…In PT and SP units, anthropogenic pressures such as fishing (bottom trawl and mean fishing), seabed litter, sst, ssl, ph, and marine traffic explained food webs trends. Similar results were found by Korpinen et al (2021) for this region, identifying global warming (increasing sst), fisheries and shipping (underwater noise) as the major challenges that need to be addressed when considering cumulative anthropogenic effects. This region is characterized by narrow shelf areas (Korpinen et al, 2021), were trawling activities occur more intensely (Eigaard et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In PT and SP units, anthropogenic pressures such as fishing (bottom trawl and mean fishing), seabed litter, sst, ssl, ph, and marine traffic explained food webs trends. Similar results were found by Korpinen et al (2021) for this region, identifying global warming (increasing sst), fisheries and shipping (underwater noise) as the major challenges that need to be addressed when considering cumulative anthropogenic effects. This region is characterized by narrow shelf areas (Korpinen et al, 2021), were trawling activities occur more intensely (Eigaard et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…Similar results were found by Korpinen et al (2021) for this region, identifying global warming (increasing sst), fisheries and shipping (underwater noise) as the major challenges that need to be addressed when considering cumulative anthropogenic effects. This region is characterized by narrow shelf areas (Korpinen et al, 2021), were trawling activities occur more intensely (Eigaard et al, 2017). Studies on the ratio of the trawling footprint over the landings showed that the highest ratios occurred in the Iberian Portuguese area, reflecting the higher level of exploitation when compared with some of the Atlantic management areas where fishing effort has been reduced (Eigaard et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Due to their small size and isolation, island and endemic species are more likely to extinguish than continental or nonendemic species [58]. Moreover, the human activities that mainly affect the marine environment usually take place in coastal areas, whose extension is limited and where the highest marine productivity is reached [57,59].…”
Section: Implications For Marine Biodiversity Conservation and Managementmentioning
confidence: 99%